Performance of the Nordmøre grid in shrimp trawling and potential effects of guiding funnel length and light stimulation - Larsen, Roger B.; Herrmann, Bent; Sistiaga, Manu Berrondo; Brinkhof, Jesse; Tatone, Ivan; Langård, Lise (Marine and Coastal Fisheries, 2017)
Source at https://doi.org/10.1080/19425120.2017.1360421 . Accepted manuscript version, licensed CC BY-NC-ND 4.0 The introduction of the Nordmøre grid to shrimp trawls has reduced the issue of bycatch to that of small-sized species and juveniles that are able to pass through the grid and enter the small-meshed cod end together with the targeted shrimp. This study estimated the size- and species-selective performance of the Nordmøre grid in the configuration most often applied by fishermen and made a preliminary exploration of the effects of reducing the length of the guiding funnel in front of the grid and mounting light-emitting diodes (LEDs) around the escape exit. Experimental fishing trials were conducted in the Barents Sea to assess the size-selective properties of a 19-mm bar spacing Nordmøre grid, mandatory in this Norwegian trawl fishery targeting deepwater shrimp Pandalus borealis (also known as northern shrimp), and its potential improvement. Results were obtained for the target species and four bycatch species: redfish Sebastes spp., Haddock Melanogrammus aeglefinus, Atlantic Cod Gadus morhua, and American Plaice Hippoglossoides platessoides. In general, very few deepwater shrimp were found to escape through the escape exit, although the quantity increased slightly at larger sizes. Between 80% and 100% of the bycatch species up to a species-specific size passed through the grid and entered the cod end. A short guiding funnel decreased this for Haddock significantly by increasing the fraction of small Haddock seeking the escape exit. Further, adding LEDs around the escape exit significantly negated this effect. For the other bycatch species, the results indicated similar trends but were not statistically significant. However, considering that only a few fishing hauls were conducted using the short guiding funnel with or without mounting LEDs calls for some caution when attributing these changes to the configuration of the Nordmøre grid, and these preliminary results should be followed up by further ...